Pengaruh Fatherless Terhadap Academic Resilience Anak Sekolah Dasar - Fajar, Rizka Putri Ayuning Lestari; Rostika, Raden Deti; Herlambang, Yusuf Tri (Jurnal Kajian Gender dan Anak, 2024)
AbstractThis study was motivated by the fact that fathers did not fulfill their roles optimally for their children due to the physical or psychological absence of the father, which is known as fatherless. Fatherless can have a negative impact on children. One of them is the impact on children's education which is closely related to academic resilience. This study aims to determine the effect of fatherless on the academic resilience of elementary school children. This study was conducted through a quantitative approach with a descriptive method. Data collection was carried out by distributing questionnaires and interviews. The questionnaires were distributed to high-grade children, namely grades IV, V and VI, and interviews were conducted with teachers. The number of child participants involved was 94 children with 9 teachers from three elementary schools in Bandung City. The results of this study prove that there is an influence between fatherless and the academic resilience of elementary school children at SDN 069 Cipamokolan Derwati, SDN 263 Rancaloa and SDN 122 Cijawura, meaning that children's perceptions of their father's absence contribute 14.4%. The implication given from this study is that the presence of a father figure is a valuable moment for children, so education is needed to provide as much information as possible about the role of the father. AbstrakPenelitian ini dilatarbelakangi dari tidak maksimalnya ayah menjalankan perannya untuk anak akibat dari ketidakhadiran ayah secara fisik atau psikologis yang disebut sebagai fatherless. Fatherless dapat memberikan dampak yang buruk bagi anak. Salah satunya berdampak pada pendidikan anak yang erat kaitannya dengan academic resilience. Penelitian ini bertujuan untuk mengetahui pengaruh fatherless terhadap academic resilience anak sekolah dasar. Penelitian ini dilakukan melalui pendekatan kuantitatif dengan metode deskriptif. Pengumpulan data dilakukan dengan penyebaran kuesioner dan wawancara. Kuesioner dibagikan kepada anak kelas tinggi yakni kelas IV, V dan VI serta wawancara dilakukan kepada guru. Jumlah partisipan anak yang terlibat sebanyak 94 anak dengan 9 guru dari tiga sekolah dasar di Kota Bandung. Hasil penelitian ini membuktikan terdapat pengaruh antara fatherless terhadap academic resilience anak sekolah dasar SDN 069 Cipamokolan Derwati, SDN 263 Rancaloa dan SDN 122 Cijawura, artinya persepsi anak akan ketidakhadiran ayah berkontribusi sebesar 14.4%. Implikasi yang diberikan dari penelitian ini adalah kehadiran figur ayah menjadi momen berharga bagi anak, sehingga diperlukan edukasi untuk memberikan informasi sebanyak-banyaknya akan peran ayah.